Model of Employee Engagement: Case Study of PT Timah (Persero) Tbk - Kuncoro, Nur Adi; Gustomo, Aurik (The Indonesian Journal of Business Administration, 2014)
Abstract – PT Timah Tbk need for high employee commitment and engage to support company vision, mission, and goals. We conduct a research about variables affecting employee engagement to be able to create solution and implementation for improvement. Questionnaires were distributed to Bangka, Belitung and Kundur districts using stratified sampling method at echelon 3 position level to non-echelon level. Analysis used to find out effects of each variable is SEM (Structural Equation Modelling). The results suggest that leadership, organization culture, recognition, work focused, and compensation are dominant variables having effects on the employee engagement. Highest loading factor value is organization culture variable. Organization culture of PT Timah Tbk has alteration appropriate to vision, mission, and external or internal environmental conditions. It is change have not completely concerived by employees. Solution to be made is to perform socialization from lowest level to senior managers and leaders give examples of organization cultural application to employment. Keywords : Employee Engagement, Organization Culture, Structural Equation Modelling